1992
DOI: 10.1159/000126255
|View full text |Cite
|
Sign up to set email alerts
|

Phenoxybenzamine Selectively and Irreversibly Inactivates Dopaminergic D<sub>2</sub> Receptors on Primary Cultured Rat Lactotrophs

Abstract: Lactotrophs have several different kinds of receptors, such as dopaminergic D2, somatostatin, angiotensin II and thyrotropin-releasing hormone receptors, which stimulate or inhibit prolaction release. We have studied the specificity of phenoxybenzamine on receptors in lactotrophs. Phenoxybenzamine is a β-haloalkylamine which alkylates chemically active radicals such as hydroxy, sulfhydryl, and amino groups. This alkylation is an irreversible chemical reaction in contrast to the receptor-secretagogue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…therefore, inactivated the do paminergic Di-receptors with phenoxybenzamine prior to studying the stimulatory action of catecholamines on prolactin release. Phenoxybenzamine was chosen since it blocks irreversibly and its half-recovery time is greater than 2 h [13]. Competitive antagonism, on the other hand, allows the receptors to return to normal function immediately after removal of the antagonist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…therefore, inactivated the do paminergic Di-receptors with phenoxybenzamine prior to studying the stimulatory action of catecholamines on prolactin release. Phenoxybenzamine was chosen since it blocks irreversibly and its half-recovery time is greater than 2 h [13]. Competitive antagonism, on the other hand, allows the receptors to return to normal function immediately after removal of the antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Since phenoxybenzamine inactivates both the a-adrenergic receptors and the Di-receptors [13], and since epinephrine, an a-|b and D:-receptor agonist, stimula tion of prolactin release from phenoxybenzamine pre treated cells likely involves the |breceptor. It is interesting to note that elevated prolactin release induced by isopro terenol, a relatively pure |breceptor agonist, returned to a basal concentration during the isoproterenol perifusion period in nonphenoxybenzamine-treated control groups, but pretreatment with phenoxybenzamine enhanced the stimulatory effect of isoproterenol on prolactin release for a longer period of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure of D 2 receptorexpressing cells (e.g. GH 4 C 1 -hD 2s ) to the receptor alkylating compound, phenoxybenzamine, for 1 h could abolish D 2 receptors (38), and we showed that the treatment markedly reduced the DA-mediated inhibition of prolactin release from primary cultured rat pituitary cells while phenoxybenzamine pretreatment was ineffective on somatostatin-, TRH-, and angiotensin-II-induced prolactin release (33). Our observation that phenoxybenzamine inactivates DAinduced prolactin release, is consistent with our prevous studies (33).…”
Section: Prolactin Release Is Usually Inhibited By Approximately 10mentioning
confidence: 93%
“…We selected three wellestablished D 2 receptor agonists (dopamine, apomorphine and bromocriptine) to investigate whether the DA-induced stimulatory effect on prolactin secretion in GH 4 ZR 7 cells is unique to DA, or if it is a general phenomenon of other DA agonists. In addition, we used a dopamine D 2 receptor antagonist (haloperidol) and an alkylating agent (phenoxybenzamine) of aadrenergic and DA receptors (33) to confirm that all the observed dopaminergic actions were indeed mediated via activation of dopamine D 2 receptors on the GH 4 ZR 7 cells.…”
Section: Introductionmentioning
confidence: 93%